Use of unmanned aerial vehicles to monitor the performance of work on scattered construction sites and ways to further implement them in construction in Ukraine - Zeltser, R.; Kolot, M.; Panasyuk, I. (Ways to Improve Construction Efficiency, 2021)
The article covers the improvement of organizational and technological solutions of construction production through the use of unmanned aerial vehicles and special software for remote control of construction of scattered facilities (for example, the construction of cottages in Kyiv region), the experience of using UAVs. Innovative approaches to the control of the life cycle of construction projects at the stages of engineering surveys and design works, zero cycle, construction of the above-ground part and further operation using drones and special software give the Ukraine construction sector companies a unique chance to realize their potential during the digital revolution and take their rightful place among world leaders. Due to the lack of operational, accurate data and indicators that describe the state of the construction site, companies face such problems as management’s lack of up-to-date information on the project implementation progress, late detection of actual of the progress of work performed from design documentation, uncontrolled human factor in the process of checking volumes and quality of works performed by contractors, insufficient communication between project participants. Subsequently, these factors lead to budget overruns and non-compliance with the estimated project deadlines. The experience of using UAVs in addressing such issues as the management’s lack of relevant information on state of affairs at construction site, late identification of actual deviations from the project documentation, uncontrolled influence of human factor in the process of checking the volume and quality of work performed by contractors, and insufficient communication between project participants. Based on the practical experience gained in the use of drones, it was concluded that drones are an effective tool with a wide range of applications for monitoring zero-cycle work and erection of the above-ground part of buildings.